Asuhan Kebidanan Continuity Of Care - amelia, fitra; Marcel, Marcel (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Pregnancy and childbirth is a physiological thing, if not managed properly and correctly it will become pathological.Continuity of care includes integrated services for mothers and children from pre-pregnancy to childbirth, postnatal period and childhood. The purpose of this research providing continuous care to Mrs. E aged 32 years multipara at PMB Evi Apriani. The results showed that the care provided from pregnancy, childbirth, postpartum and newborn all went smoothly and the condition of mother and baby was good and healthy. Conclusion, after being given continuity of care from pregnancy, childbirth, postpartum and newborn all went smoothly and the condition of the mother and baby was normal.Suggestions for health workers to maintain the quality of health services and early screening to determine continuous obstetric care and quality of service.